Preparing accountants of the future: examining an accounting data and analytics undergraduate program in Singapore - SEOW, Poh Sun (Institutional Knowledge at Singapore Management University, 2024)
Due to technological innovations, there is a need for universities to produce accounting graduates who are proficient in data and analytics, in addition to core accounting skills. A university in Singapore launched the accounting data and analytics (AD&A) second major program to provide students with skillsets in data and analytics. The aim of this study is to examine the efficacy of the AD&A program. 100 participants were surveyed, involving 70 graduates of the program and 30 employers. The results show that both graduates andemployers were satisfied with the program. The results also show that the program adequately equips graduates with relevant skills and competencies, reflecting current needs in the accounting profession. This study is timely as the need for accountants to become more techsavvy and conversant with data has been identified as an important way to help the accounting profession thrive amid digital transformation.